2016
DOI: 10.1007/978-3-319-32274-2_16
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Fruit Softening

Abstract: Ripe kiwifruit have a soft melting texture that, combined with distinctive flavours, aromas and colours, has made the fruit an international success. A key feature of successful New Zealand cultivars, e.g. Actinidia chinensis var. deliciosa 'Hayward' and Actinidia chinensis var. chinensis 'Hort16A', is their ability to be stored for long periods both at ambient temperature and in cool storage. In these cultivars, the majority of fruit softening occurs in the apparent absence of ethylene production. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 106 publications
(123 reference statements)
0
6
0
Order By: Relevance
“…It is well documented that cell wall disassembly is caused by the synergistic actions of a multitude of cell wall enzymes. In kiwifruit 'Hayward', the activities of cell wall associated enzymes and the change of cell wall component have been extensively studied [8,9,33]. It is mainly concluded that the activity of PG enzyme increases with ripening process and becomes abundant when fruit ripen [11,12], although a slight increase of PG activity during kiwifruit softening was previously reported [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well documented that cell wall disassembly is caused by the synergistic actions of a multitude of cell wall enzymes. In kiwifruit 'Hayward', the activities of cell wall associated enzymes and the change of cell wall component have been extensively studied [8,9,33]. It is mainly concluded that the activity of PG enzyme increases with ripening process and becomes abundant when fruit ripen [11,12], although a slight increase of PG activity during kiwifruit softening was previously reported [10].…”
Section: Discussionmentioning
confidence: 99%
“…Accompanied with the kiwifruit softening progress, the change of cell wall composition and the activities of cell wall enzymes occurred [8,9]. The main biochemical changes include pectin solubilisation, galactose loss, soluble pectin degradation, and a reduction in the molecular weight of xyloglucan [9]. The change of PG activity during 'Hayward' softening have been described previously [10][11][12], but their results seemed somewhat contradictory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kiwifruit is an unusual climacteric fruit as many ripening processes, including the majority of fruit softening, occur independently of climacteric ethylene ( Richardson et al., 2011 ). Climacteric (endogenous) ethylene production starts at the last stage of kiwifruit ripening ( Atkinson and Schroder, 2016 ), when fruit is becoming eating-soft, but can also be induced by exogenous ethylene or chilling exposure ( Minas et al., 2016 ). When ethylene is suppressed, the last stages of ripening including the production of aroma volatiles do not occur ( Atkinson et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…For producers, however, providing fruit during the optimum window of consumption can be challenging. Fruit softening that occurs too quickly affects shelf life, is susceptible to physical injury and pathogen attack as well as increases transport and storage costs . Hence, there are strong economic drivers for understanding the fruit softening process.…”
Section: Introductionmentioning
confidence: 99%